Impact of Smart Cities on Urban Resilience: The Roles of Land Green Utilization Efficiency and Industrial Structure Transformation - Chaobo Zhou; Xinting Li (Land, 2025)
Relying on information technologies such as the Internet, big data, and cloud computing, smart cities (SC) fully integrate urban resources, constantly strengthen the ability of urban economic systems, infrastructure systems, ecosystems, social systems, institutional systems, and other systems to withstand disaster disturbance and external risk shocks, and promote urban resilience (UR) construction. This study uses panel data from 254 prefecture-level cities in China from 2009 to 2021, and employs a multiperiod difference-in-differences method to examine the direct and heterogeneous effects of SC on UR. After a series of empirical tests, this study obtains the following results: (1) SC have a significant impact on the improvement of UR, which objectively demonstrates the reciprocity between SC and the level of UR construction, providing data support for promoting the in-depth practice of SC. (2) From the mechanism test of the impact of SC on UR, urban land green utilization efficiency and industrial structure transformation are intermediate mechanisms through which SC affect the improvement of UR. In addition, public environmental attention (PEA) has a positive regulatory effect on SC and UR, that is, PEA strengthens the role of SC in improving UR. (3) From the heterogeneity of urban characteristics that affect UR, SC have a more significant effect on improving UR in eastern cities and non-resource-based cities. This study provides new ideas for studying UR and provides useful insights for promoting SC construction and enhancing UR. This study proposes that the government should continue to promote the intelligent construction of Chinese cities, advance the industrial structure and improve the green land utilization efficiency, and strengthen their positive impact on UR.